EFEKTIFITAS KINERJA PEJABAT FUNGSIONAL SATUAN POLISI PAMONG PRAJA PROVINSI LAMPUNG DALAM PENCEGAHAN PENYEBARAN COVID-19 - Malik Malik; Ida Farida; Muhammad Alhusnuriski (e-JKPP, 2021)
The existence of such rapid social change movements in people's lives requires anticipation in the form of increased competence and capacity of Satpol PP personnel and institutions that are able to respond to these changes. This is also intended so that unnecessary social collisions and losses can be suppressed in such a way. With such competencies and abilities, it is hoped that Satpol PP duties will be more professional, have minimal social losses, succeed in accordance with the objectives of local government policies, and get full support from the community. In order to increase the capacity of human resources and optimize the performance of Satpol PP, the Government has established a Civil Service Police Functional Position based on the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform Number 4 of 2014 concerning the Functional Position of the Civil Service Police and its Credit Score. The data collection techniques in this study are observation, interview and documentation. There are 7 informants in this study (objectives) people. The research method uses qualitative research methods. In general, the results of the study are that the implementation of the performance of functional officials at the Satpol PP of Lampung Province in an effort to prevent the spread of COVID-19 in Lampung Province is quite effective because based on the indicators in measuring the improvement in performance that have been described, the role of functional officials is highly correlated with these activities. activities carried out in the midst of a pandemic that occurred, so that the implementation of functional activities synergized with prevention efforts carried out by the Satpol PP of Lampung Province.